Assessment of burden and needs of family caregivers for the elderly, a scoping review - Le Toullec, Elodie; Le Gagne, Anne; Leblong, Emilie; Somat, Alain; Piette, Patrice (Frontiers in Aging, 2025)
BackgroundFamily caregivers play a central role in supporting older adults. Their role is complex and challenging. Their assessment is essential for planning support systems. This review aims to catalog the different scales, identify the spectrum of dimensions they cover, and evaluate their psychometric quality, with the aim of reflecting on potential clinical recommendations.MethodA systematic review of MEDLINE, PsycINFO, google scholar and CINAHL databases identified tools for measuring family caregiver engagement. Two reviewers selected relevant studies using predefined criteria. Keywords included “family caregivers,” “engagement,” “measurement,” and “psychometrics.” Extracted data was analyzed for reliability, validity, and other psychometric properties.ResultsWe identified 140 articles, 38 of which were analyzed, utilizing 29 different scales to assess caregiver support across various dimensions such as burden, stress, or needs. Clinimetric assessment using an abbreviated COSMIN checklist revealed significant variability in the reliability and validity of these scales, with only 2 meeting clinical research standards. Notable deficiencies were found in internal consistency, reproducibility, and construct validity. None of the scales cover the entire range of complex dimensions associated with family caregivers.ConclusionThe study underscores the need for improved measurement tools tailored to the complexities of caregiver engagement. Future work should focus on developing more refined scales that better capture the diverse needs of family caregivers to enhance support.